(untitled) (Journal of Asian Development Studies, 2023)
In 1996, an organization was formed by the name Shanghai Five, which was later transformed into the Shanghai Cooperation Organization (hereinafter SCO) with a current total of nine members. It is an international alliance with an agenda to work and cooperate for a better and peaceful world from a social, economic, security and environmental perspective. The policy of the SCO is entirely based upon the principles of mutual benefit, mutual trust, equal rights, recognition and respect for diverse cultures and aspirants towards joint development. SCO has been facing various issues in terms of legal framework. From time to time, international observers and researchers have highlighted several things that SCO had to work on in furtherance of what the international community expects from such an organization. However, SCO can be seen by how rapidly it has improved from five-member organizations, having no say in the world, to aa significant organization which now has an essential and positive role in governing various matters in the region and at the international level. It has positively reflected in the term of the legal framework and has shown a satisfying future ahead by the international rules and policies. In the instant research, all the issues mentioned above, specifically in the context of the legal framework of SCO, were addressed further. Other international organizations’ legal frameworks were discussed, and a guiding path could be adopted. It is pertinent to mention that the internal rivalry in SCO is also an issue. Most of the time, it is the subject of discussion whenever the SCO matters are under discussion. Other member countries must play their part in solving every case by contributing their factors.